A 20-Year Research Trend Analysis of the Influence of Anesthesia on Tumor Prognosis Using Bibliometric Methods - Luo, Jiamei; Shi, Yumiao; Wang, Xiaoqiang; Zhang, Ruirui; Chen, Sifan; Yu, Weifeng; Su, Diansan; Tian, Jie (Frontiers in Oncology, 2021)
Background. Bibliometric analysis is used to gain a more systematic understanding of developments in the field of the influence of anesthesia on tumor prognosis and changes in research hot spots over the past 20 years. Methods. Relevant publications from the Web of Science Core Collection (WoSCC) were downloaded on October 1, 2020. Acquired data were then analyzed via bibliometric analysis using the Online Analysis Platform of Literature Metrology (http://biblimetric.com) and the CiteSpace software to analyze and predict trends and hot spots in this field. Results. 1,492 publications on the influence of anesthesia on tumor prognosis were identified. The leading country in this field were the United States of America (USA). Pennsylvania State University (State College, PA, USA) and the University of Texas MD Anderson Cancer Center (Houston, TX, USA) featured the highest number of publications among all institutions. Co-citation cluster labels revealed characteristics of eight main clusters: opioid growth factor (OGF), tumor growth, cancer recurrence, local anesthetics, volatile anesthesia, potential mechanism, human neoplasia, and opioid use. Keyword burst detection indicated that local anesthetics, randomized controlled trials (RCTs), and volatile anesthetics were the newly emerging research hot spots. Conclusions. This study compiled 1,492 publications covering anesthesia and tumor prognosis research and showed that the direction of these studies may transition from a clinical phenomenon to a basic mechanism. It provided guidance for further research and clinical applications on choosing anesthetic methods and drugs.